Linear adaptive structure for control of a nonlinear MIMO dynamic plant - Bańka, Stanisław; Dworak, Paweł; Jaroszewski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
In the paper an adaptive linear control system structure with modal controllers for a MIMO nonlinear dynamic process is presented and various methods for synthesis of those controllers are analyzed. The problems under study are exemplified by the synthesis of a position and yaw angle control system for a drillship described by a 3DOF nonlinear mathematical model of low-frequency motions made by the drillship over the drilling point.
Keywords: MIMO multivariable control systemsmultivariable control systems; nonlinear systems; modal control